Are the steam tables dead? - Müller,EA (Chemical Engineering Education, 2009)
Erich A. Müller has discussed about the book steam tables, a special tabulations of volumetric and energetic properties of saturated and superheated water, with a very fine grid of temperatures and pressures to allow precise calculation of the thermodynamic properties of water. These steam tables are also available as spreadsheet plug-in as commercial and academic stand-alone programs for PCs and as a phone applications to allow the precise and efficient determination of thermophysical properties of a rather significant amount of fluids. He also discussed the problem using computer programs in which the brain ceases to perform its usual analytical functions and accepts the response from the electronic instrument without questioning. He suggested that the chemical engineering have to deal with a few sparse data or an odd table, so as to estimate the data.